Cold Interests, Hot Conflicts: How a Professional Association Responded to a Change in Political Regimes - Nunez-Carrasco, E (Springer Publishing Company, 2019)
In South America, the 1970s began with ardent sociopolitical crises leading to a wave of repressive military regimes. In Chile, most professional bodies suffered profound structural and functional modifications resulting from internal political polarization as well as state intervention. Nurses saw the same fate befall them, which created both a historical blackout and abrupt changes in power dynamics. Given the prominence of this process in the reconfiguration of modern nursing’s identity, this article traces the association’s political process during the short-lived 1970s Marxist-inspired government and the response of nurses collectively to the rapid shift into a repressive regime leading to a profound internal crisis and an identity break-up within nursing. By using archival sources and oral testimonies 1 of 1970s and 1980s nurses, we reconstruct a historical account of a key period in the history of the country that for the nurses meant a progression of discord and division along with a self-imposed silence on the past. In so doing, the article adds to a growing literature on the participation of women in political life. © 2019 Springer Publishing Company.